SCAMPER SEBAGAI STRATEGI MENULIS KREATIF BAHASA ARAB ABAD 21 - Risna Rianti Sari; Ahmad Mubaligh (Arabi : Journal of Arabic Studies, 2019)
Recent study assumed that SCAMPER is an effective technique to foster creative thinking skill. SCAMPER can also used in Arabic learning process especially for writing skill among Arabic education students. The purpose of this study was to shed some light about creative writing in learning Arabic writing by SCAMPER. Qualitative method was used in this research which includes 3 steps; there are data reduction, data display and conclusion drawing. The creative Arabic writing by SCAMPER can be held during class by applying 2 steps. First, the lecturer explained about SCAMPER (substitute, combine, adapt, modify, put in other use, eliminate and reverse); then secondly, the lecture prepared a topic or text. After lecturer’s role, it was the students’ turn to explore the text and create the new text by following step of SCAMPER. It is concluded that creativity can be learned during class and SCAMPER can help the students to enhance creative writing skill.